Peter Paul Rubens - Varshavskaya, Maria (Best of, 2014)
Universally celebrated for his rosy and concupiscent nudes, Peter Paul Rubens (1577-1640) was an artist whose first concern was sensuality in all its forms. This Baroque master devoted himself to a lifelong celebration of the joys and wonders of the physical realm. He felt that the human body was as lovely and natural as the many natural landscapes he painted as a young man. In a lushly illustrated text, María Varshavskaya and Xenia Yegorova explore the master at work, bringing a unique focus to Ruben's life and work